2023
DOI: 10.1097/pas.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

International Society of Urological Pathology (ISUP) Consensus Conference on Current Issues in Bladder Cancer

Antonio Lopez-Beltran,
Maria R. Raspollini,
Donna Hansel
et al.

Abstract: Emerging data on T1 bladder cancer subcategorization (aka substaging) suggests a correlation with oncological outcomes. The International Society of Urological Pathology (ISUP) organized the 2022 consensus conference in Basel, Switzerland to focus on current issues in bladder cancer and tasked working group 3 to make recommendations for T1 subcategorization in transurethral bladder resections. For this purpose, the ISUP developed and circulated a survey to their membership querying approaches to T1 bladder can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Significant progresses have been made in bladder carcinoma pathology over the last decade. The ISUP Consensus Conference on Current Issues in Bladder Cancer 5–8 offers a comprehensive literature review with practical recommendations and guidance for future research in the field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant progresses have been made in bladder carcinoma pathology over the last decade. The ISUP Consensus Conference on Current Issues in Bladder Cancer 5–8 offers a comprehensive literature review with practical recommendations and guidance for future research in the field.…”
Section: Discussionmentioning
confidence: 99%
“…T1 bladder carcinomas show high variability in clinical behavior. Although reporting of T1 subcategorization is strongly encouraged by several guidelines, the premeeting ISUP survey revealed that it is not a common practice 7 . The methodologies for T1 subcategorization can be separated roughly on the basis of histoanatomic landmarks and semiquantitative assessment.…”
Section: Main Findings and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations